Umbilical cord blood stem cells as third-party adjuvant infusions in human leukocyte antigen antibody-positive patients undergoing haploidentical hematopoietic stem cell transplantation - Wang, Yuying; Zhao, Yiou; Fang, Xiaosheng; Yuan, Dai; Ding, Mei; Lu, Kang; Qu, Huiting; Wang, Na; Lv, Xiao; Li, Peipei; Zhen, Changqing; Xu, Hongzhi; et al. (Frontiers in Immunology, 2024)
Graft failure (GF) or poor graft function (PGF) remain critical obstacles in haploidentical hematopoietic stem cell transplantation (haplo-HSCT), especially in recipients with HLA antibodies. Here, we performed a retrospective cohort study to investigate the efficacy and safety of the use of unrelated umbilical cord blood stem cells (UCBs) as a third-party adjuvant infusion in patients with HLA-antibodies undergoing haplo-HSCT. A total of 90 patients were divided into three groups: 17 patients in Group A (with positive HLA antibodies and who received UCB infusion), 36 patients in Group B (with positive HLA antibodies without UCB infusion), and 37 patients in Group C (without HLA antibody or UCB infusion). The median age of patients included in Groups A, B, and C was 43 (IQR, 27 -49.5), 33 (IQR, 20 -48.75), and 30 (IQR, 18 -46.5) years, respectively. All but one patient in Group B achieved granulocyte recovery within 28 days after transplantation. The median time to granulocyte engraftment were all 12 days for patients in Groups A, B, and C, respectively. All the patients in Group A achieved 100% donor chimerism without UCB engraftment. There were no significant differences in granulocyte or platelet engraftment time between the three groups. There were 1, 5, and 0 patients in Groups A, B, and C, respectively, who developed PGF. The cumulative incidence rates for any grade of acute graft-versus-host disease (aGVHD) were comparable among the three groups. Patients in Group B presented a greater incidence of cGVHD than did those in Group A (P = 0.002) and Group C (P = 0.006). Patients in Group A presented more limited and milder cGVHD than those in Group C (P < 0.0001). The 1-year relapse-free survival (RFS) was 70.6% (95% CI, 0.47 -0.87), 55.6% (95% CI, 0.40 -0.70), and 77.9% (95% CI, 0.63 -0.89) in Groups A, B, and C, respectively. Our results indicated that patients who were positive for HLA antibodies were at a greater risk of developing GF/PGF. Co-infusion with UCBs was safe and improved engraftment, cGVHD, and improved the 1-year RFS to some extent.